2011
DOI: 10.1016/j.jvs.2010.10.068
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular chimney technique versus open repair of juxtarenal and suprarenal aneurysms

Abstract: Ch-EVAR may extend the anatomical eligibility of endovascular aneurysm repair using conventional devices. It appears to have similar mortality to open repair with less morbidity. Long-term durability and stent patency remain to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
154
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(159 citation statements)
references
References 41 publications
4
154
1
Order By: Relevance
“…Nonetheless, permanent dialysis occurred only in open surgery patients (9.5%). 78 In a recent comparable study with a population of 90 consecutive JRA patients, early mortality and permanent hemodialysis have been reported as higher in the endovascular arm (chimney and fenestrated repair) versus open repair arm (0% vs 6.4% and 0% vs 6.5%, respectively). 40 In another similar study (50 consecutive JRA patients undergoing fenestrated or chimney repair), early mortality did not differ between groups (8%); however, renal complications including deterioration of renal function (> 50% rise in serum creatinine) and renal infarction were considerably higher in the chimney group (25% vs 13% and 25% vs 8%, respectively).…”
Section: Hybrid Chimney and Snorkel Repairsmentioning
confidence: 90%
See 1 more Smart Citation
“…Nonetheless, permanent dialysis occurred only in open surgery patients (9.5%). 78 In a recent comparable study with a population of 90 consecutive JRA patients, early mortality and permanent hemodialysis have been reported as higher in the endovascular arm (chimney and fenestrated repair) versus open repair arm (0% vs 6.4% and 0% vs 6.5%, respectively). 40 In another similar study (50 consecutive JRA patients undergoing fenestrated or chimney repair), early mortality did not differ between groups (8%); however, renal complications including deterioration of renal function (> 50% rise in serum creatinine) and renal infarction were considerably higher in the chimney group (25% vs 13% and 25% vs 8%, respectively).…”
Section: Hybrid Chimney and Snorkel Repairsmentioning
confidence: 90%
“…76 This approach, which is considered as another off-theshelf solution, can also be used as a bailout from accidental coverage of vital side branches during deployments requiring close approximation of the main body to the branch artery in question. 36,77,78 Elective indications include JRAs or aneurysms with severely angulated necks, when alternative techniques and/or devices are not options. 57 The chimney technique fundamentally differs from fenestrated and branched EVAR with regards to the relationship of the visceral stents to the aortic SG.…”
Section: Hybrid Chimney and Snorkel Repairsmentioning
confidence: 99%
“…On the other hand, some authors have reported that bare stents are not inferior to covered stents with regard to renal patency or protection against type Ia ELs. 16) Furthermore, in Japan, are only able to use bare stents for Ch-EVAR due to national insurance coverage. Thus, the existing data have not provided any firm conclusions as to whether these devices were associated with an increased risk of type Ia EL.…”
Section: Discussionmentioning
confidence: 99%
“…The brachial sheath was then pulled back, and the chimney stent was deployed. 7) Thereafter, simultaneous balloon molding was performed using a compliant aortic balloon in the endograft and reinflation of the balloon of the renal stent ( Fig. 2A and 2B).…”
Section: The Endowedge and Snorkel Techniquesmentioning
confidence: 99%